2013
DOI: 10.12988/ams.2013.310587
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy risk analysis based on Ochiai ranking index with Hurwicz criterion for generalized trapezoidal fuzzy numbers

Abstract: In this paper, we present a new method for ranking generalized trapezoidal fuzzy numbers (GTrFNs) based on Ochiai index and Hurwicz criterion. The proposed ranking method considers all types of decision makers' perspective such as optimistic, neutral and pessimistic which is crucial in solving decision-making problems. The proposed method can discriminate the ranking result of GTrFNs having the same mode and symmetric spread. Two observations obtained from the proposed method are presented. Some numerical exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The concept of decomposed fuzzy numbers is used to execute the fuzzy arithmetic operations on these Quasi-Gaussian fuzzy numbers and the process of conversion and execution of arithmetic operations has been explained in a later section of this paper. The technique used for determining the minimum of two decomposed fuzzy numbers using the concept of lattice of fuzzy numbers and α -cuts is preferred over other ranking methods like those discussed in the paper by Ramli and Mohamad (2009) using the centroid index that falls under the category of fuzzy scoring techniques. These centroid indexes can be used for ranking of triangular and trapezoidal fuzzy numbers as most of it involves calculating the area under the curve which requires less number of calculations in case of triangular and trapezoidal fuzzy numbers and more calculations when Gaussian fuzzy numbers are involved, thereby increasing the complexity of the operations.…”
Section: Problem Formulationmentioning
confidence: 99%
“…The concept of decomposed fuzzy numbers is used to execute the fuzzy arithmetic operations on these Quasi-Gaussian fuzzy numbers and the process of conversion and execution of arithmetic operations has been explained in a later section of this paper. The technique used for determining the minimum of two decomposed fuzzy numbers using the concept of lattice of fuzzy numbers and α -cuts is preferred over other ranking methods like those discussed in the paper by Ramli and Mohamad (2009) using the centroid index that falls under the category of fuzzy scoring techniques. These centroid indexes can be used for ranking of triangular and trapezoidal fuzzy numbers as most of it involves calculating the area under the curve which requires less number of calculations in case of triangular and trapezoidal fuzzy numbers and more calculations when Gaussian fuzzy numbers are involved, thereby increasing the complexity of the operations.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Asady and Zendehnam [3] advised a point nearest to the origin as a de-fuzzified value for the fuzzy number. A review of centroid index ranking methods was reported by Ramli and Mohamad [16]. Various centroid ranking methods are considered and compared showing the fact that no single method in the centroid concept is superior to all other methods since each method appears to have some advantages as well as disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the limitations of previous studies, Osman et al (2019) proposed the use of FCM based on fuzzy numbers. Fuzzy numbers depict the physical world more realistically and can produce attribute weights at different levels of confidence (Dom, Hasan, Shahidin, & Apandi, 2019;Sulaiman et al, 2017;Ramli & Mohamad, 2009). Nonetheless, Osman et al (2019) used Patra and Mondal (2015)'s similarity measure based on area, height, and distance, which cannot differentiate the degree of similarity for some different pairs of fuzzy numbers.…”
Section: Introductionmentioning
confidence: 99%